Short-range order, bulk moduli, and physical trends in c-si1-xcx alloys - Kelires, Pantelis C. (My University, 1997)
Alloys of silicon and carbon in the crystalline phase, although complex and with varying degrees of short-range order, are shown to exhibit an accurate power-law dependence of the bulk modulus B on the average nearest-neighbor separation d, over the whole composition range. The homopolar energy gap of these alloys increases with carbon content. Similar trends have only been proposed earlier for the much simpler diamond and zinc-blende semiconductors.
Keywords: Alloys; Silicon; Carbon; Semiconductors; Zinc